Assessment of knowledge and skills of cold chain handlers in the post-eVIN period in nainital district - Chaudhary, Kunal; Awasthi, Sadhana; Maroof, Mohammad; Kanubhai, Thakkar Hemaben; Mohd. Najmul Aqib Khan; Preeti; Kaur Anand, Kanakmeet (Asian Journal of Medical Sciences, 2023)
Background: Vaccines are among the most sensitive drugs; they are sensitive to heat and freezing; therefore, they must be stored at the recommended temperature. Thus, it is deemed necessary to study staff’s knowledge and skill level about the modified cold chain of electronic vaccine intelligence network (eVIN) period. Aims and Objectives: The study aims to assess the knowledge and skills of Cold Chain Handlers regarding cold chain, eVIN and vaccine management in district Nainital. Materials and Methods: This cross-sectional study was carried out at 34 Cold Chain Points in district Nainital, Uttarakhand. Pre-structured validated questionnaire was used for this study. Results: Cold chain handlers were deputed at all cold chain points of which about one-third was contributed by the Haldwani block. All 29 females and five males cold chain handlers were literate and mostly had received eVIN training. It was found that except for knowledge about adverse event following immunization, its primary management, hold over time, and keeping dropper in ice-lined refrigerator rest was correctly answered by all of them and skills about the identification and performing tasks were performed splendidly by all 34 (100°). Conclusion: Cold chain handlers need reinforcement in skills and keeping knowledge up to date to keep the cold chain healthy and properly functioning.